Coordinated motion control of a dual-arm space robot with joint-limit avoidance and uncertain inertial parameters. (7th September 2017) - Jiao, Chunting; Liang, Bin; Wang, Xueqian; Song, Jingyan; Zhang, Bo
In this article, a new adaptive coordinated motion control approach is introduced for a dual-arm free-floating space robot. This adaptive algorithm is used for the post-capture of a large noncooperative target with joint-limit avoidance and uncertain dynamic parameters. To overcome the problem of dynamics coupling between the space base, its manipulators, and the target, we develop a dual-arm space robotic system. One arm is used to complete the capture task and the other is used to counteract the disturbance to the space base. In this case, a new coordinated motion control law is derived based on reaction null space control. An improved joint-limit avoidance algorithm is implemented for large noncooperative target capture; otherwise, a significant base disturbance may result if the joint-limit constraints are not explicitly considered. Based on momentum conservation, the linear regression form of the estimation problem is obtained, and we further identify the unknown inertial parameters of the target. Finally, the simulation results demonstrate the effectiveness of the proposed algorithm.